Vaccination with novel low-molecular weight proteins secreted from Trichinella spiralis inhibits establishment of infection. - Mellina T Srey; Alessia Taccogna; Yelena Oksov; Sara Lustigman; Pei-Yi Tai; John Acord; Murray E Selkirk; Tracey J Lamb; David B Guiliano (Public Library of Science (PLoS), 2020)
Trichinella spiralis muscle stage larvae (mL1) produce excretory-secreted products (ESPs), a complex mixture of protein, which are believed to be important for establishing or maintaining an infection niche within skeletal muscle and the intestine. Studies of both whole ESPs and individual cloned proteins have shown that some ESPs are potent immunogens capable of eliciting protective immune responses. Here we describe two novel proteins, Secreted from Muscle stage Larvae SML-4 and SML-5 which are 15 kDa and 12 kDa respectively. The genes encoding these proteins are highly conserved within the Trichinellids, are constituents of mL1 ESP and localized in the parasite stichosome. While SML-5 is only expressed in mL1 and early stages of adult nematode development, SML-4 is a tyvosylated glycoprotein also produced by adult nematodes, indicating it may have a function in the enteral phase of the infection. Vaccination with these proteins resulted in an impaired establishment of adult stages and consequently a reduction in the burden of mL1 in BALB/c mice. This suggests that both proteins may be important for establishment of parasite infection of the intestine and are prophylactic vaccine candidates.